The impact of gadget use for medical education during covid-19 pandemic on neck pain, neck disability, and sleep quality among medical students in Indonesia - Pepi Budianto; Dewi Hayu Kirana; Muhammad Hafizhan; Stefanus Erdana Putra; Diah Kurnia Mirawati; Hanindia Riani Prabaningtyas (Intelektual Pustaka Media Utama, 2022)
During the COVID-19 pandemic, nation-wide social restriction policy is implemented to prevent virus spread. Medical students are relying on gadget and internet-based services for online learning. Prolonged use of gadget is related to various medical condition. This study aims to determine correlation between duration of gadget use and their relationship to neck pain, neck disability, and sleep quality among medical student. This was a cross-sectional study conducted using Numeric Pain Rating Scale (NRS), Oswestry Disability Index (ODI), and Pittsburgh Sleep Quality Index (PSQI) in online form. Sample was selected with simple random sampling from the population of medical student of Universitas Sebelas Maret, entrance year of 2017-2020. Results: A total of 271 students were included in this study. Statistically significant correlation between duration of gadget uses and neck pain (p=0,014); neck disability (0.471,p=0.042); and sleep quality (0.571,p=0.023). Duration of gadget use increased the incidence of neck pain by 3.028 times (95% CI 2.272-4.327,p=0.037); incidence of neck disability by 2.144 times (95% CI 1.174-3.461,p=0.015); and decreased sleep quality by 2.384 times (95% CI 1.107-3.661,p=0.007). Duration of gadget use increased the incidence of neck pain, neck disability, and decreased sleep quality of medical student. Awareness of the importance of proper ergonomics while using gadget for medical education during COVID-19 pandemic should be raised among students, lecturers, and healthcare professional.